1988
DOI: 10.1007/bf01645066
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of urinary tract infections — Amoxicillin induces genital escherichia coli colonization

Abstract: The aim of this study was to examine whether a vaginal Escherichia coli colonization, mimicking the one seen in UTI-prone females, could be induced by amoxicillin administration. In adult cynomolgus monkeys, who carry the alpha-Gal-1-4-beta-Gal receptor for P-fimbriae, we have investigated the ability of a clinical isolate of P-fimbriated E. coli to colonize the mucous membranes of the genital tract. When the vagina was washed with a suspension of the P-fimbriated strain, a persistent colonization was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This can be explained by the defense mechanism of these boys not being sufficiently developed to prevent recolonization. It is also possible that antibiotic treatment can decrease the host colonization resistance by disturbing the ecological balance in the periurethral region (18). The pattern was different among girls.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the defense mechanism of these boys not being sufficiently developed to prevent recolonization. It is also possible that antibiotic treatment can decrease the host colonization resistance by disturbing the ecological balance in the periurethral region (18). The pattern was different among girls.…”
Section: Discussionmentioning
confidence: 99%
“…All 16 monkeys were outbred. The procedure has been described in detail elsewhere (17,21,22). In summary, a catheter was introduced into the vagina, and 3 ml of an E. coli suspension (10 9 CFU/ml) with either DS17, DS17-8, or DS17-1 was flushed over the mucous membranes.…”
Section: Methodsmentioning
confidence: 99%
“…This can be the reason for vaginal pH modifications and a subsequent alteration of the composition of the vaginal microflora in those women. 16) Some other studies have reported on modification of the normal microflora due to hormone treatment or influences: Herthelius et al 17) have suggested that the estrogens in monkeys and humans produce changes which would favor lactobacilli colonization of the vaginal tract. Marrie et al 18) have shown that the percentage of Lactobacillus colonization in women increases during menarche and pregnancy, and decreases after menopause.…”
Section: Discussionmentioning
confidence: 99%